KUALITAS LAPORAN KEUANGAN DAN PENGENDALIAN INTERNAL, TERHADAP EFISIENSI INVESTASI - I Made Pradana Adiputra (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2018)
This study aims to analyze the relationship between the quality of financial statements and over/ under-investment and the influence of the quality of financial statements on over/under-investment with the disclosure of the level of internal control in listed and non-listed state-owned companies in Indonesia. The research sample was listed and non-listed BUMN in Indonesia with 208 firms-years during 2011-2016 with linear regression analysis using the SPSS program. The regression test results show that there is support for the hypothesis of this study, namely that the quality of financial statements negatively affects over/under-investment and the effect of the quality of financial statements on over/under-investment is stronger in SOEs that disclose their internal controls. To strengthen the results of the research, additional testing was conducted to analyze the differences between listed SOEs and non-listed SOEs. The results show that listed SOEs have more explanatory power on the effect of the quality of financial statements on over/under-investment than non-listed SOEs. That is because listed SOEs must also follow capital market regulations (Indonesia Stock Exchange) and market mechanisms that relate to investors and other external parties who have an interest in the operation (performance) of these SOEs.